2023
DOI: 10.1093/bbb/zbad168
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and utilization of novel aldoxime, nitrile, and nitro compounds metabolizing enzymes from plants and arthropods

Takuya Yamaguchi

Abstract: Aldoxime (R1R2C=NOH) and nitrile (R−C≡N) are nitrogen-containing compounds that are found in species representing all kingdoms of life. The enzymes discovered from the microbial “aldoxime-nitrile” pathway (aldoxime dehydratase, nitrile hydratase, amidase, and nitrilase) have been thoroughly studied because of their industrial importance. Although plants utilize cytochrome P450 monooxygenases to produce aldoxime and nitrile, many biosynthetic pathways are yet to be studied. Cyanogenic millipedes accumulate vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In bioactivation process, amygdalin is hydrolyzed to form mandelonitrile by amygdalin hydrolase (AH) and prunasin hydrolase (PH) [ 27 , 31 33 ], and then hydrolyzed by mandelonitrile lyase (MDL) to form benzaldehyde with release of HCN [ 34 ]. Several plants have evolved various different detoxification mechanisms, with the most effective pathway that is the conversion of HCN into β-cyanoalanine by β-cyanoalanine synthase (β-CAS), and then hydrated by nitrilases (NITs) to generate asparagine or aspartate along with ammonia [ 2 , 27 , 35 ]. All these indicated that mandelonitrile was one key intermediate for both biosynthesis and bioactivation of amygdalin involved in several regulatory enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In bioactivation process, amygdalin is hydrolyzed to form mandelonitrile by amygdalin hydrolase (AH) and prunasin hydrolase (PH) [ 27 , 31 33 ], and then hydrolyzed by mandelonitrile lyase (MDL) to form benzaldehyde with release of HCN [ 34 ]. Several plants have evolved various different detoxification mechanisms, with the most effective pathway that is the conversion of HCN into β-cyanoalanine by β-cyanoalanine synthase (β-CAS), and then hydrated by nitrilases (NITs) to generate asparagine or aspartate along with ammonia [ 2 , 27 , 35 ]. All these indicated that mandelonitrile was one key intermediate for both biosynthesis and bioactivation of amygdalin involved in several regulatory enzymes.…”
Section: Introductionmentioning
confidence: 99%